Physiological and morphological factors affecting leaf sheath reinforcement and their contribution to lodging resistance in rice - Tomohiro Nomura; Satoshi Ohkubo; Atsushi J. Nagano; Ahmad Fahim Samadi; Shunsuke Adachi; Taiichiro Ookawa (Plant Production Science, 2023)
ABSTRACTIn rice (Oryza sativa L.), leaf sheaths enhance stem strength and lodging resistance. However, little is known about the factors that affect varietal differences and changes over time regarding leaf sheath reinforcement. In the present study, the morphological and physiological traits that are presumed to be related to leaf sheath reinforcement were examined in ‘Chugoku 117’ and ‘Koshihikari’, rice varieties with high and low degrees of leaf sheath reinforcement, respectively. The results showed that Chugoku 117 had thicker leaf sheaths and delayed leaf sheath senescence than Koshihikari, indicating that there were clear varietal differences in these traits. The bending moment at breaking with leaf sheath was correlated with senescence-associated traits, especially strongly correlated with the number of living leaf sheaths in both varieties. Among the components examined in the present study, only starch content was significantly positively correlated with both varieties. On the other hand, the starch in the leaf sheath disappeared in the latter stage of ripening due to translocation to sinks, suggesting that it contributes to stem strength only up to the early stages of ripening. The findings suggest that rice stem strength can be increased by thickening the leaf sheaths and delaying leaf sheath senescence. Thus, in addition to the physical properties of the culm, such as shortening (semi-dwarfing) and strengthening, the findings of the present study provide a new breeding strategy for improving breaking-type lodging resistance in rice.